Recurrence of COVID-19 Infection in Healthcare Workers after complete Vaccination - Aqsa Naseer, Madeeha Nazar, Jamila Khan, Humera Nasim, Mujeeb Khan, Nida Anjum, Muhammad Umar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 is a novel infection. Since its first case report in 2019, it has affected population globally. Healthcare workers are at most risk as they are in direct contact with patients. Aim: To record recurrence of symptomatic COVID 19 after complete doses of Sinopharm vaccine among healthcare workers. Study design: Descriptive case series Place and duration of study: Department of Gastroenterology, Holy Family Hospital, Rawalpindi from 12th December 2021 to 11th June 2022. Methodology: Twenty four healthcare workers and between 20-60 years who had COVID-19 infection previously and despite receiving two doses of Sinopharm vaccine, again developed symptomatic COVID-19 diseases were enrolled. The severity was graded as per guidelines provided by CEAG. The extent of exposure during work was documented. Results: No significant association was found with any of the healthcare workers with duration and extent of vaccination. Upto 66% of the front line workers got COVID at 5th month and no considerable variation was noticed in other months of the vaccination. Similarly, three PGs also got COVID at 5th month and at 5th month highest number of frontline workers got COVID-19. Conclusion: COVID-19 reinfection can occur even after vaccination though symptoms remain relatively mild and Sinopharm provides protection against severe infection for prevention of COVID-19. Keywords: COVID, Recurrence, Health workers, Vaccination, Infection